Acute Glomerulonephritis in a Child with Chlamydia pneumoniae Infection: A Case Report. (18th July 2013) - Vitaliti, Giovanna; Falsaperla, Raffaele; Giunta, Leandra; Spataro, Giuseppina; Rapisarda, Venerando; Velardita, Mario; Nunnari, Giuseppe; Pavone, Piero
Abstract : Background . Infectious diseases seem to be an important and independent risk factor for renal failure, but the underlying mechanism of renal involvement during some kinds of infectious diseases is still unclear, even if the literature data report immunomediated and/or autoimmune mechanisms to explain the pathogenic relationship between the two diseases. In paediatric patients, Chlamydia pneumoniae is a rare cause of renal complications and it may manifest in several ways, mainly involving the respiratory system, even if also renal and glomerulalr complications, have been described. Case Diagnosis/Treatment . Herein we report a case of a 3-year-old child who developed an acute glomerulonephritis that was chronologically, clinically, and biologically related to a previous Chlamydia pneumoniae infection. On our knowledge, in the literature it is the youngest patient with renal involvement during course of Chlamydia pneumoniae infection ever reported. Conclusions . The present case supports the hypothesis of a rather close causal relationship between this infective agent and renal and glomerular symptoms occurred in this child, during an acute episode of respiratory disease.